Perbandingan Konsep Riba dan Bunga Bank Menurut Quraish Shihab Dan Mutawalli As-Sya’rowi Serta Relevansinya Terhadap Perbankan Indonesia - Awan, Edi; Mubarok, Imam Anas; Saniatin, Any; Firdaus, Jannatul; Arifah, Hertin Khalifatun Nisa; Fauziyah, Hanifah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
Banks exist as the economic powerhouse of mankind humanity. Problems have arisen regarding the banking system, which has narrowed down to interest, thus becoming a controversial topic of discussion. This causes differences of opinion among scholars such as Quraish shihab and Mutawalli as-sya'rowi. This difference of opinion regarding the status of interest can affect public interest in conducting transactions with banks. Objective This study aims to determine the comparison of the concepts of usury and bank interest according to Quraish shihab and Mutawalli as-sya'rowi. according to Quraish shihab and Mutawalli as-sya'rowi and its relevance to Indonesian banking. Indonesian banking. The research method used is qualitative method with literature study. Based on the results of the research, the law of interest according to Quraish Shihab is not something haram. Shihab is not something that is haram, considering that the current interest does not contain elements of persecution and oppression. contain elements of persecution and oppression between human beings. The method Quraish's method of legal istinbath takes four main steps, namely looking at the asbab nuzul of the verse, looking for keywords, quoting the opinions of previous scholars, and contextualizing and comparing them. and contextualizing and comparing usury with bank interest practices that occur today. that occurs at this time. The method of istinbâth ahkam used by Mutawalli as-sya'rowi in determining the status of interest is the Qur'an. Mutawalli as-sya'rowi's thinking that the practice of usury is forbidden in Islam because it is not in accordance with the purpose of the law of a contract and transactions with usury practices only provide comfort to one party only. only provides comfort to one party only. Keywords: Riba, Mutawalli As-Sya'rowi, Quraish Shihab, Indonesian Banking